School Memories about Homophobic Bullying: A Study Based on Cultural-Historical Psychology - da Silva, Rômulo Lopes [UNESP]; de Souza, Vera Lucia Trevisan (MDPI, 2023)
The expression of homophobic violence in schools reveals the urgency of an analytical approach to debate the impact of this phenomenon on students' mental health. This article seeks to debate and better comprehend school memories from young gays, lesbians, and bisexuals, as well as to discuss how homophobic bullying affected their school trajectories. This study is based on cultural-historical psychology in intersection with gender and sexuality studies. In-depth online interviews were conducted with three young subjects who identified themselves as non-heterosexual. The interviews were recorded, transcribed, and analyzed through the analytical discourse tool defined as Nuclei of Meanings. The results were organized in two topics of discussion: (a) the problems associated with non-heterosexual identity in schools; (b) the search for other ways of experiencing sexual identity in school. Throughout the article, reflections were held about the challenges participants had to deal with in order to regularly attend school and be educated, as well as the obstacles they faced in building their own ways of recognizing their sexual identity. The unique ways in which these young subjects took a stand in the face of homophobic situations show new methods to create educational interventions in order to include sexual diversity and openness to different possibilities of being and acting.